Problems drafting of land use to establish the limits restrictions in the use of land and the object with regime - Dorosh, Y.; Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2017)
Analyzed the legal framework of restrictions in land use and their regime facilities (laws, regulations, rules, regulations, standards and classifications. Found that the current classification provides for the conduct of State Land Cadastre is flawed because it does not cover all kinds of restrictions, making impossible to use it for practical purposes.Therefore, we proposed territorial restrictions in the use of land classified by types and species.The classification confirms expediency to distinguish meaningful component of the project land to establish limits restrictions in land use and their rezhymoutvoryuyuchyh objects from the standard procedure of development for all types of project documentation provided by the Law of Ukraine "On Land Management".The article contains an updated block model for the drafting of land to establish the limits of restrictions on land use and regime facilities.The project land boundaries to establish restrictions on land use and regime facilities include:1) drafting task on land;2) an explanatory note;3) the decision of the local government of drafting;4) characterization of the natural environment;5) certificate containing a summary of land (territory);6) Cartogram agro-industrial groups of soils and steep slopes;7) geodetic surveys and materials of Land Management8) information on the current state of land use and protection (including registered in the State Land Cadastre restrictions on land use;9) description of the territory by establishing usage of land of natural reserve fund and other environmental protection, health, recreational, historical, cultural, forestry purposes, land and water resources protection zones, restrictions in land use and their regime facilities;10) within the limits the settlement - a copy of the graphic part of the master plan of settlement (if applicable), and outside the village - a copy of the appropriate planning documentation (if any) and a copy of the decision on the approval of such documentation;11) information on the prospective state of land use and protection within the administrative unit, which is part of land management schemes and technical economic assessment of land use and protection relevant administrative unit (if any);12) plan of the territory of mapping land, landowners and land users;13) list of operating facilities;14) plan limits land use restrictions on the types and species;15) land management regulations;16) decision on approval of land management projects on delineating restrictions on land use and their regime facilities.Keywords: land management, land management projects, land use, restrictions in land use, regime facilities.